A Comparative Study on the Application of Quality Assessment Schemes in Academic and Construction Industries - Balasubramanian, M; Selvan.S, Senthil; R.Prasath Kumar, V; S, Mahadevan (International Journal of Engineering and Technology, 2018)
In this study, the development of professionalism of undergraduate students of civil engineering is essential to face the challenges in the modern world and this study describes professional internship program for each semester in the civil engineering department at SRM Institute of Science and Technology. Based upon literature reviews of the professional internship program for each semester questionnaires are prepared and given to faculties, undergraduates of SRM Institute of Science and Technology and also get from the construction contractors, to predict issues in the traditional professional internship program. For undergraduates questionnaires consider weighted percentage of before and after professional internship program are Wb and Wa. The expert groups were utilized to planning, implementation, evaluation, and execution of the professional internship program at the SRM Institute of Science and Technology. An implementation of the professional internship program for each semester of undergraduate students of the civil engineering department at SRM Institute of Science and Technology. The outcomes obtained for civil engineering undergraduates are getting from valuable resources, that professional internship program for each semester is needed undergraduates to develop the carrier and gain knowledge and should create best civil engineers.Â Â Â